PELATIHAN MANAJERIAL DAN TEKNIS PENGELOLAAN INDUSTRI KECIL MEBEL DAN UKIR Dl SENTRA INDUSTRI MULYOHARJO JEPARA - SARWIDO SARWIDO; BUDI LOFIAN (Universitas Islam Nahdlatul Ulama Jepara, 2010)
Abstract Jepara cant be locked out by furniture and carving industries, it even have been conceived by society life breath. This Sector have become to aorta economics area and become activator of society economics. Middle and small furniture and carving industries in Central Mulyohaijo Jepara Industry are economic perpetrator portraits of nationality which supporting local human resource and input, descending emulation excellence of export commerce. Manajerial and technical management training middle and small furniture and carving industries flanges to: reinforcement of its which delay progressively and grow from market extension side, resource enables efficiency and give multiplier effect.